2020
DOI: 10.5664/jcsm.8350
|View full text |Cite
|
Sign up to set email alerts
|

Low repeatability of Epworth Sleepiness Scale after short intervals in a sleep clinic population

Abstract: Study Objectives: The purpose of this study was to evaluate the short-term repeatability of the Epworth Sleepiness Scale (ESS) in patients with suspected obstructive sleep apnea and to determine whether transitory sleepiness of the patient influenced ESS results. Methods: Adult participants with suspected obstructive sleep apnea taking part in a study on the diagnostic accuracy of repeated sleep studies were eligible. For assessment of repeatability, the agreement between 2 sequential ESS scores obtained withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(55 reference statements)
1
11
0
2
Order By: Relevance
“…This is because it has been shown that ESS alone may not be enough to evaluate daytime sleepiness (Thorarinsdottir et al, 2019). The ESS is known for its low repeatability and test–retest reliability even during a single day (Campbell et al, 2018; Grewe et al, 2020), and its low sensitivity and specificity to identify the presence of OSA (AHI ≥ 5) highly depends on the used ESS cut‐off value (Rosenthal & Dolan, 2008). Among the general population, the median ESS was found to be 6 points (Stradling et al, 2000), while among patients with OSA the score was 7.8, 8.3 and 9.3 for mild, moderate and severe OSA, respectively (Gottlieb et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This is because it has been shown that ESS alone may not be enough to evaluate daytime sleepiness (Thorarinsdottir et al, 2019). The ESS is known for its low repeatability and test–retest reliability even during a single day (Campbell et al, 2018; Grewe et al, 2020), and its low sensitivity and specificity to identify the presence of OSA (AHI ≥ 5) highly depends on the used ESS cut‐off value (Rosenthal & Dolan, 2008). Among the general population, the median ESS was found to be 6 points (Stradling et al, 2000), while among patients with OSA the score was 7.8, 8.3 and 9.3 for mild, moderate and severe OSA, respectively (Gottlieb et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy may be enhanced when the ESS is completed as a consensus between the patient and partner [46]. Recent data have questioned the reliability of the ESS [43,44,47,48]. One study found variability in ESS scores even when the assessment was repeated on the same day, suggesting that situational sleepiness (i.e.…”
Section: Self-report Assessments Of Edsmentioning
confidence: 99%
“…One study found variability in ESS scores even when the assessment was repeated on the same day, suggesting that situational sleepiness (i.e. time of test administration) may influence ESS scores [48].…”
Section: Self-report Assessments Of Edsmentioning
confidence: 99%
“…Grewe et al 1 have raised questions about the commonly used Epworth Sleepiness Scale (ESS) in medicine. They report discrepancies of at least 2 points between sequential ESS scores that occurred in 63%, at least 3 points in 48%, at least 5 points in 20%, and at least 7 points in 8% of the total of 40 participants.…”
mentioning
confidence: 99%